2021
DOI: 10.3390/diagnostics11091714
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Diabetes Mellitus Using Gradient Boosting Machine (LightGBM)

Abstract: Diabetes mellitus (DM) is a severe chronic disease that affects human health and has a high prevalence worldwide. Research has shown that half of the diabetic people throughout the world are unaware that they have DM and its complications are increasing, which presents new research challenges and opportunities. In this paper, we propose a preemptive diagnosis method for diabetes mellitus (DM) to assist or complement the early recognition of the disease in countries with low medical expert densities. Diabetes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(69 citation statements)
references
References 44 publications
(55 reference statements)
0
47
0
Order By: Relevance
“…To our knowledge, this was the first study that targeted the elderly population (≥65 years) in China to build predictive models for diabetes using machine learning techniques, which would have great implications for designing diabetes prevention focusing on the elderly. With the development of artificial intelligence, machine learning techniques have been widely applied in the medical field, especially for prediction models for diabetes [ 49 , 51 , 53 , 56 , 57 , 58 ]. It is worth noting that the advantages of machine learning models are well-documented empirically compared with traditional statistical methods, but its disadvantage is the lack of model interpretability [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this was the first study that targeted the elderly population (≥65 years) in China to build predictive models for diabetes using machine learning techniques, which would have great implications for designing diabetes prevention focusing on the elderly. With the development of artificial intelligence, machine learning techniques have been widely applied in the medical field, especially for prediction models for diabetes [ 49 , 51 , 53 , 56 , 57 , 58 ]. It is worth noting that the advantages of machine learning models are well-documented empirically compared with traditional statistical methods, but its disadvantage is the lack of model interpretability [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the LightGBM model has better predictive performance for the classification of etiological types of patients with classic FUO. LightGBM is a distributed gradient lifting framework based on a decision tree algorithm, which has high efficiency and performance in dealing with binary classifications and multi-classification problems (44)(45)(46). LightGBM is an ensemble algorithm developed by Microsoft, which is superior to other machine learning methods for disease diagnosis in many cases (45).…”
Section: Discussionmentioning
confidence: 99%
“…LightGBM is a distributed gradient lifting framework based on a decision tree algorithm, which has high efficiency and performance in dealing with binary classifications and multi-classification problems (44)(45)(46). LightGBM is an ensemble algorithm developed by Microsoft, which is superior to other machine learning methods for disease diagnosis in many cases (45). Fundamentally, this is achieved by combining multiple base classifiers into an ensemble model by learning the inherent statistics of the combined classifiers and, hence, outperforming the single classifiers.…”
Section: Discussionmentioning
confidence: 99%
“…The gradient boosting machine (GBM), a machine learning algorithm for regression and classification, can train many models in order. Then, each new model updates the prediction using the gradient descent method [ 16 20 ]. GBM has shown great success in a wide range of practical applications and can be highly customized to the application's specific needs, gradually minimizing the loss of function.…”
Section: Introductionmentioning
confidence: 99%